(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the history of Khoja Ubban and Khoja Zafaran shrines, located in Romitan district of Bukhara region, as well as information about the fact that these shrines are healing places, are researched based on scientific sources and field research materials. The research work is based on the principle of historicity, chronological and comparative analysis methods.